PENGARUH PROFITABILITY, LEVERAGE, SIZE DAN CAPITAL INTENSITY RATIO TERHADAP EFFECTIVE TAX RATE PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD & BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Pasha, Dina; Nafiah, Zumrotun; hendrayanti, silvia (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Effective tax rate is the effective tax level in the form of a percentage of tax that must be paid by taxpayers based on the company's income or gross profit after considering various tax deductions in accordance with applicable tax regulations. This research aims to determine the influence of profitability, leverage, size and capital intensity ratio on the effective tax rate in manufacturing companies in the Food & Baverage Sub Sector listed on the Indonesia Stock Exchange in 2018-2022. The total population in this study was 88 companies. The total sample for this research was 32 companies taken using the purposive sampling method. The variables used in this research are profitability, leverage, size, capital intensity ratio and effective tax rate. The results of the analysis show that the profitability and leverage profitability variables influence the effective tax rate (ETR). Meanwhile, the variables size and capital intensity ratio have no effect on the effective tax rate. Meanwhile, the variables profitability, leverage, size, capital intensity ratio of 86.9% have an influence on the effective tax rate, and 13.1% are influenced by other factors not included in this research. It is recommended that further research expand the research year period and company sector and use proxies or other measuring tools so that the results obtained are different and more accurate, adding independent variables that are not included in this research